Statistical analysis of Cymbopogon chemical compounds for oils species / Khairul Anis Athirah Kamarulzaini … [et al.] - Kamarulzaini, Khairul Anis Athirah; Ismail, Nurlaila; Jamil, Mailina; Mohd Ali, Nor Azah; Lias, Sahrim; Taib, Mohd Nasir (Universiti Teknologi MARA Press (Penerbit UiTM), 2020)
Cymbopogon essential oil is extracted from the Cymbopogon species which are citronella and lemongrass. This situation may cause confusion and mistake by the selection of the planters. This essential oil is commonly used as aromatherapy and pharmacological activities such as anti-bacterial. The compounds identified in this Cymbopogon oils are mainly geraniol, citronellal, citronellol, geranyl acetate, linalool, limonene and germacrene D. The paper aims to summarize the statistical analysis of Cymbopogon chemical compounds between citronella and lemongrass for oils species by using SPSS software. This study consists of data extraction for the oils species using GC-MS machine to identify their chemical compounds. Then, statistical analysis data was performed which consist of the values of abundances. Next, the descriptive statistics data was carried out by evaluating the minimum and maximum data, mean, standard deviation, variance and kurtosis. The result showed that geraniol compound achieved the highest value of abundances and descriptive statistics for both datasets compared to other compounds because it has a role as a fragrance, an allergen and a plant metabolite. This is proven that statistical analysis and descriptive statistics in this study were able to summarize the preliminary data of Cymbopogon oil compounds according to its species which are lemongrass and citronella.